2018
DOI: 10.26508/lsa.201800084
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cnot6l in maternal mRNA turnover

Abstract: Mice lacking Cnot6l, a deadenylase component of the CCR4–NOT complex, are viable, but females have ∼40% smaller litters. Cnot6l is a maternal-effect gene acting in maternal mRNA degradation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 45 publications
1
54
0
Order By: Relevance
“…Consistent with our findings, a recent study that was published while this manuscript was in revision reported decreased female fertility of Cnot6l ‐null mice. The study showed that in oocytes and zygotes derived from Cnot6l −/− mice, the timely degradation of maternal mRNA is perturbed (Horvat et al , ). However, the oocyte maturation process of Cnot6l ‐null oocytes was not observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, a recent study that was published while this manuscript was in revision reported decreased female fertility of Cnot6l ‐null mice. The study showed that in oocytes and zygotes derived from Cnot6l −/− mice, the timely degradation of maternal mRNA is perturbed (Horvat et al , ). However, the oocyte maturation process of Cnot6l ‐null oocytes was not observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Significant progress has recently been made in understanding the regulation of mRNA stability in mammalian oocytes and zygotes. CNOT6L, which is a catalytic subunit of CCR4-NOT deadenylase, and its associated zinc finger protein 36-like 2 (ZFP36L2) protein were found to be essential for mRNA decay that accompanies oocyte meiotic maturation 6 – 8 . The B-cell translocation gene-4 (BTG4), which is an oocyte-specific adapter protein of CCR4-NOT, was identified as an MZT-licensing factor in mice that mediated mRNA clearance prior to ZGA 9 – 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Mouse genome contains several L1 families, of which LINE1_Md_A, LINE1_Md_T(-F) and LINE1_Md_G(-F) are the most recent and contain full-length retrotransposition-competent LINE1 copies [59][60][61]. We examined expression of all full-length L1 elements with intact ORF in the reference C57Bl/6 genome in fully-grown oocytes by mapping our C57Bl/6 RNA-seq libraries directly on these elements (using RNA-seq of wild type oocytes from this work and from [62]). Perfectly mapping 50 nucleotide single end sequencing (50SE) showed low abundance of reads for the most expressed L1 elements from different families (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…) in fullygrown GV oocytes (125 PE from GSE116771[62], 50 SE from this work), RNA-seq reads were mapped onto genome with all sequences except the 2691 L1 elements masked. Only reads perfectly mapping to those sequences were retained 23.…”
mentioning
confidence: 99%